Strengthening EFL Teacher Collaboration in the “New Normal”: Leveraging the Use of Online Resources - Artanti Puspita Sari (Jurnal Bahasa dan Sastra, 2020)
Abstract: The burden of maintaining the continuity of education amid Covid-19 pandemic highlights the necessity to increase English as a Foreign Language (EFL) teacher collaboration. This article aims to present a review of literature concerning the benefis and challenges of teacher collaboration, forms of teacher collaboration practices, and the roles of educational leaders in fostering teacher collaboration. Then, it explores possible ways in leveraging online resources to support teachers’ collaborative activities. Results of the literature review shows that teachers’ collaborative effrts effctively support their professional development and improve students’ achievement despite several challenges. Some of the challenges are teachers’ lack of time management, inability to provide and receive feedback, inability to appoint collaborative leaders, limited leadership support, defiiency in pedagogical knowledge, and limited technological access and skills. Collaborative practices include peer coaching, pedagogical discussions, sharing of teaching materials, peer observation, pair mentoring, and study groups. Existing literature also shows that the support of educational leaders toward teacher collaboration leads to better teachers’ professional development and students’ achievement. In addition, the review indicates that online platforms serve as powerful media for collaborative activities. Based on the review of literature, several implications are drawn with regards to the roles of schools, teachers, teacher education institutions, the government, and possibilities for future research.Keywords: Teacher collaboration, New Normal, Online ResourcesAbstrak: Beban menjaga keberlangsungan pendidikan akibat pandemi Covid-19 mengharuskan para guru Bahasa Inggris sebagai bahasa asing untuk meningkatkan kegiatan berkolaborasi. Artikel ini bertujuan untuk menyajikan kajian pustaka mengenai manfaat dan tantangan kolaborasi guru, bentuk-bentuk aktifias dalam kolaborasi guru, dan peran pemimpin institusi/ organisasi pendidikan dalam membina kolaborasi guru. Tulisan ini juga mengeksplorasi berbagai cara yang dapat dilakukan dalam rangka memanfaatkan sumber daya online untuk kegiatan kolaboratif. Hasil tinjauan pustaka menunjukkan bahwa kolaborasi guru efektif dalam pengembangan profesionalisme guru dan peningkatan prestasi siswa walaupun terdapat beberapa tantangan dalam implementasinya. Beberapa tantangan yang dihadapi adalah kurangnya kemampuan guru dalam mengatur waktu, ketidakmampuan dalam memberikan dan menerima umpan balik, ketidakmampuan untuk menunjuk pemimpin dalam kelompokkelompok kolaboratif, terbatasnya dukungan pemimpin, kurangnya pengetahuan pedagogis dan akses terhadap teknologi, serta terbatasnya keterampilan menggunakan teknologi. Bentuk aktifias kolaboratif guru termasuk peer coaching, diskusi mengenai pembelajaran, berbagi bahan pengajaran, peer observation, pair mentoring, dan kelompok belajar. Literatur yang ada menunjukkan bahwa dukungan pemimpin institusi/organisasi pendidikan terhadap kolaborasi guru berdampak pada pengembangan profesional guru dan peningkatan prestasi siswa. Selain itu, pustaka yang ada juga menunjukkan bahwa media online menunjang kegiatan kolaboratif guru. Berdasarkan kajian literatur terhadap kolaborasi guru, disimpulkan beberapa implikasi sehubungan dengan peran sekolah, guru, lembaga pendidikan keguruan, pemerintah, dan kemungkinan arah penelitian ke depan.Kata-kata Kunci: kolaborasi guru, kenormalan baru, media dalam jaringan